Calidad de servicio y satisfacción del cliente de la empresa transportes Los Goyos EIRL, Punchana 2023 - Lemos Panduro, Melissa de Jesus (2023)
The objective of this 2023 research was to establish the relationship between outstanding service quality and user satisfaction in the transportation company "Los Goyos." The research adopted a quantitative approach, employing a design that analyzes correlations, following a cross-sectional approach without experimental interventions. To achieve this goal, two surveys were administered to a set of 25 regular customers of the company. The results obtained indicated that there is an extremely positive and strong connection between service excellence and customer satisfaction (correlation coefficient r = 0.918; p < 0.005). In summary, it was confirmed that a significant link between service quality and customer satisfaction exists within the company.